CT volumetry helps predict prognosis of large hepatocellular carcinoma after resection. Issue 8 (August 2022) - Lian, D.; Wang, W.; Liu, L.; Wang, J.; Rao, S.; Zhou, J.
Abstract : AIM: To determine whether the tumour volume measurement on preoperative contrast-enhanced computed tomography (CT) could be used to predict the overall survival patients with large hepatocellular carcinoma (>5 cm) after resection. MATERIALS AND METHODS: This study included 171 patients with surgically confirmed hepatocellular carcinoma who underwent preoperative CT. The largest diameter, the product of the axial dimension, tumour volume, and tumour-to-liver volume ratio (TTLVR) on CT images were measured and calculated. The univariate and multivariate Cox proportional hazard ratio regression models were used to identify the impact of the tumour burden-related risk factors on overall survival. RESULTS: In multivariate analysis, TTLVR ( p= 0.042) and major vascular invasion ( p= 0.006) were independently associated with overall survival of patients with hepatocellular carcinoma after the resection. The group in which the patients had a low TTLVR showed higher cumulative survival rates than patients with a TTLVR ( p= 0.004). Patients with a low TTLVR (≤26.23%) and absence of major vascular invasion had significantly higher cumulative survival rates compared to those patients with hepatocellular carcinoma with either or both the risk factors ( p= 0.001). CONCLUSION: A higher TTLVR in combination with the presence of major vascular invasion was associated with poorer overall survival in patients with large hepatocellular carcinoma after resection. Highlights: Using tumour to liver volume ratio (TTLVR) to quantify tumour burden of large HCC. TTLVR of large HCC was measured on preoperative CT. Lower TTLVR (≤26.23%) had higher cumulative survival rates than higher group. Higher TTLVR in combination with major vascular invasion present had poorer OS.